Is the Adjectival Suffix -al a Strong Suffix? - Quentin Dabouis (Anglophonia)
Within the framework introduced by Guierre (1979), this paper challenges the commonly accepted classification of the adjectival suffix -al as a strong suffix through the study of a corpus of pronouncing dictionary data enriched with additional information from other sources such as the Oxford English Dictionary. After a review of the disparities between different analyses and classifications of that suffix in the literature, it is shown that most descriptions previously proposed are problematic. We do find -al in strong endings triggering a direct computation of stress placement, but only in certain specific subclasses. A number of sets ending in -al are highly regular, but -al by itself (i.e. when it is not associated with certain elements preceding it) does not trigger direct computation systematically.